Tunisian Democracy at a Crossroads: A Comparative Analysis of Beji Caid Essebsi and Kais Saied Regimes - Lukman, Nizar (UI Scholars Hub, 2024)
As a new democracy, Tunisia is quite vulnerable to democratic erosion. The implementation of democracy in the country was quite effective during the leadership of Beji Caid Essebsi, resulting in a high democracy index driven by various policies that supported the implementation of this system. However, Tunisia’s quality of democracy significantly declined since President Kais Saied took power in 2019. The dissolution of Parliament, the prime minister's dismissal, the introduction of freedom of expression for council members, and unilateral electoral reforms aimed at consolidating his power are some cases of proof. This pattern raises questions about the recurring nature of democracy after presidential changes. Therefore, this research highlights the importance of studying the leadership traits and political beliefs of incumbent leaders in shaping the direction of democracy. This research aims to extrapolate the leadership characteristics of the two presidents, assessing their ideological orientation to determine their attitudes toward democracy and its impact. This study implements a combination of Leaders Trait Analysis (LTA) as part of a quantitative approach and Process Tracing techniques as a qualitative part by revealing public appearances (interviews and speeches) and combining them with historical events as empirical evidence that will show a comprehensive leader's personality to explain the cognitive and dispositional attributes that encompass various tendencies toward democratization.